Contributions of Onto-Materialist Studies to Interrogate an Ethnography; [Aportes de Los Estudios Onto-Materialistas Para Interrogar Una Etnografía] - Contreras-Salinas, S (Universidad Austral de Chile, 2023)
The aim of this paper is to address some premises of materialist ontology to interrogate the onto-epistemological-methodological ties, the affects/effects and the micropolitics of research. To this effect, the research trajectory of an ethnography in the field of childhood studies and power relations is analyzed. As result and conclusion of this work, it is emphasised that the proposed analytical framework, although emergent, will allow us to interrogate the research machinery, in terms of the aggregation/ specification of its investigative assemblages, as well as its effects on the capacity to be detrimental or strengthen the structures of large social and cultural formations, typical of performative research. © 2023, Universidad Austral de Chile. All rights reserved.